If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -1) = -4x + 45 Reorder the terms: 3(-1 + 4x) = -4x + 45 (-1 * 3 + 4x * 3) = -4x + 45 (-3 + 12x) = -4x + 45 Reorder the terms: -3 + 12x = 45 + -4x Solving -3 + 12x = 45 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -3 + 12x + 4x = 45 + -4x + 4x Combine like terms: 12x + 4x = 16x -3 + 16x = 45 + -4x + 4x Combine like terms: -4x + 4x = 0 -3 + 16x = 45 + 0 -3 + 16x = 45 Add '3' to each side of the equation. -3 + 3 + 16x = 45 + 3 Combine like terms: -3 + 3 = 0 0 + 16x = 45 + 3 16x = 45 + 3 Combine like terms: 45 + 3 = 48 16x = 48 Divide each side by '16'. x = 3 Simplifying x = 3
| 2x^2=-2x+4 | | 9x+15+1+13x=30 | | 4x-45=5(3x+2) | | 2(x-3)-5=-x+7 | | 9x+15+1x+23=30 | | 10n-2/5=48/5 | | 7n-6=-104 | | d=4cm | | a(-4)-[21]= | | y=x^2-8x+28 | | [13+6-(-2)]= | | -6d-(-1)= | | 10x+5a=bx-cforx | | -112q=-1608 | | -(-1)= | | 10x+5a=bx-c | | x^4-4x-45=0 | | -8+5b+3=39 | | 10h-13=56 | | 9-8+n=54 | | 4a-6=42 | | -10x+2=28 | | 9m+7=17 | | 4m+6=124 | | 3n+4-n=12n | | 10+4b=30 | | 1-0.8z^2=0 | | y=55x^2-25x+80 | | d(-3)*2= | | 40x=48(x-2) | | y=cos(2x^2) | | c/17=18 |